2007
DOI: 10.1016/j.ab.2006.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative continuous assay for hyaluronan synthase

Abstract: A rapid, continuous, and convenient three-enzyme coupled UV absorption assay was developed to quantitate the glucuronic acid and N-acetylglucosamine transferase activities of hyaluronan synthase from Pasteurella multocida (PmHAS). Activity was measured by coupling the UDP produced from the PmHAS-catalyzed transfer of UDP-GlcNAc and UDP-GlcUA to a hyaluronic acid tetrasaccharide primer with the oxidation of NADH. Using a Xuorescently labeled primer, the products were characterized by gel electrophoresis. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Recently, it was demonstrated that, for Streptococcus zooepidemicus, overexpression of genes involved in UDP-GlcNAc biosynthesis increased the molecular weight of the HA products [22], indicating that the chain length is controlled by the availability of the substrates. This is corroborated by kinetic data from HAS enzymes of different sources, demonstrating a significantly larger K MNAc value than K MUA value [23][24][25][26]. Furthermore, the hyaluronan synthase in Pasteurella multocida (PmHAS) possesses the ability to elongate HA oligosaccharides [27], which offers an additional opportunity to optimize product length and polydispersity.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Recently, it was demonstrated that, for Streptococcus zooepidemicus, overexpression of genes involved in UDP-GlcNAc biosynthesis increased the molecular weight of the HA products [22], indicating that the chain length is controlled by the availability of the substrates. This is corroborated by kinetic data from HAS enzymes of different sources, demonstrating a significantly larger K MNAc value than K MUA value [23][24][25][26]. Furthermore, the hyaluronan synthase in Pasteurella multocida (PmHAS) possesses the ability to elongate HA oligosaccharides [27], which offers an additional opportunity to optimize product length and polydispersity.…”
Section: Introductionmentioning
confidence: 53%
“…A coupled-enzyme assay, similar to assays created for other glycosyltransferases [23,31,32], was developed to measure PmHAS activity. The coupled-enzyme assay directly links the increase in the UDP by-product of the PmHAS elongation to the decrease of NADH that was spectrophotometrically measured at 340 nm.…”
Section: Characterization Of Pmhasmentioning
confidence: 99%
“…Second, because AsPc-1 tumors are heterogeneous (Bernhaus et al 2009; Tan and Chu 1984), simple histology may not provide an accurate assessment of the amounts of collagen and hyaluronic acid within the tumors. To address this limitation, we plan to use a soluble assay to quantify the collagen and hyaluronic acid content more accurately (Barnes et al 2009; Krupa et al 2007; Nagelschmidt and Viell 1987). Third, we performed all measurements with ex vivo samples; therefore, we could not assess the effects of blood pressure on Young’s modulus.…”
Section: Discussionmentioning
confidence: 99%
“…Both nucleotide sugars (UDP-glucuronic acid and UDP-N-acetylglucosamine) were added in equimolar ratio and in sufficient amount in order to initiate the polymerization and enable us to follow the elongation process in time by means of the coupled enzyme assay and agarose gel analysis. The activity of PmHS2 was assessed by measuring the UDP formation with a noncontinuous spectrophotometric assay at 340 nm (Gosselin et al 1994 ; Krupa et al 2007 ). In this assay, the UDP released from the conversion of the nucleotide sugars during the polymerization is coupled via pyruvate kinase (PK) and lactate dehydrogenase (LDH) to the oxidation of NADH into NAD + .…”
Section: Methodsmentioning
confidence: 99%